Peran Yayasan ATMA Dalam Pemberian Bantuan Hukum Bagi Anak Pelaku Tindak Pidana - O Agustin Damayanti; Rizky Rachmawan; Wiwin Mariyana (Literasi : Jurnal Kajian Keislaman Multi-Perspektif, 2020)
Many criminal acts are committed by children. They mostly do so because of external encouragement, such as family and friends at play. It is not uncommon for them to need legal assistance to defend their rights and interests in the case resolution process. The ATMA Foundation is one of the institutions that handles cases of children as perpetrators of criminal acts. Using a qualitative approach by collecting data through interviews, this study aims to determine the role of the ATMA Foundation in providing legal assistance to child perpetrators of criminal acts.Â  The results of the study explain that diversion is the main step of the ATMA Foundation so that children's rights are not violated.Â  The aim is none other than to create a child-friendly legal and judicial system.